Performance of Paracheck™-Pf, SD Bioline malaria Ag-Pf and SD Bioline malaria Ag-Pf/pan for diagnosis of falciparum malaria in the Central African Republic - Djallé, Djibrine (BioMed Central, 2014)
BACKGROUND: Rapid diagnostic tests (RDTs) are the current complement to microscopy for ensuring prompt malaria treatment. We determined the performance of three candidate RDTs (Paracheck™-Pf, SD Bioline malaria Ag-Pf and SD Bioline malaria Ag-Pf/pan) for rapid diagnosis of malaria in the Central African Republic. METHODS: Blood samples from consecutive febrile patients who attended for laboratory analysis of malaria at the three main health centres of Bangui were screened by microscopy and the RDTs. Two reference standards were used to assess the performance of the RDTs: microscopy and, a combination of microscopy plus nested PCR for slides reported as negative, on the assumption that negative results by microscopy were due to sub-patent parasitaemia. RESULTS: We analysed 436 samples. Using the combined reference standard of microscopy + PCR, the sensitivity of Paracheck™-Pf was 85.7% (95% CI, 80.8–89.8%), that of SD Bioline Ag-Pf was 85.4% (95% CI, 80.5–90.7%), and that of SD Bioline Ag-Pf/pan was 88.2% (95% CI, 83.2–92.0%). The tests performed less well in cases of low parasitaemia; however, the sensitivity was > 95% at > 500 parasites/μl. CONCLUSIONS: Overall, SD Bioline malaria Ag-Pf and SD Bioline malaria Ag-Pf/pan performed slightly better than Paracheck™-Pf. Use of RDTs with reinforced microscopy practice and laboratory quality assurance should improve malaria treatment in the Central African Republic.